1998
DOI: 10.1046/j.1365-2648.1998.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical supervision: insider reports of a private world

Abstract: An exploratory study, funded by the Department of Health, London and the Scottish Home and Health Department, Edinburgh, was conducted over an 18-month period to provide an informed view on possible assessment tools that could be used to assess the impact of clinical supervision (CS) in nursing and to report on the CS activities in 23 selected sites in England and Scotland. The study not only examined the utility of several standardized research instruments, to be reported separately, but also explored the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 10 publications
4
92
0
3
Order By: Relevance
“…In another study, supervisees confused clinical supervision with de facto CS, time out, and common sense; in fact many understood they had been partaking in CS for years (White et al, 1998). These researchers noted the tension between clinical and managerial responsibilities in regard to staff cover, managing workloads, available time, and competing clinical priorities (White et al, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, supervisees confused clinical supervision with de facto CS, time out, and common sense; in fact many understood they had been partaking in CS for years (White et al, 1998). These researchers noted the tension between clinical and managerial responsibilities in regard to staff cover, managing workloads, available time, and competing clinical priorities (White et al, 1998).…”
mentioning
confidence: 99%
“…White et al (1998) suggest that CS should exclude personal matters, unless impeding patient care. It could be said that there are more effective ways for nurses to remain psychologically healthy, such as having a work-life balance and access to counselling when required (employee assistance programs).…”
mentioning
confidence: 99%
“…It has become clear that many staff receiving supervision see stress management as an important outcome from the support that they receive during supervision sessions and one that further assists them to continue to provide high quality healthcare and avoid burn-out (Berg and Hallberg, 2000;Cross et al, 2010;Lindahl and Norberg, 2002;White et al, 1998). There is an indication that group supervision in particular can assist in managing the stressors of everyday work for health care professionals (Cross et al, 2010;Lindahl and Norberg, 2002); however, it is not clear whether other formats for supervision, such as 1:1 supervision, would provide the same benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Task oriented content was cited in all but one of the cross-sectional studies (Berg and Hallberg, 2000;Boland et al, 2010;Brunero and Stein-Parbury, 2008;Butterworth et al, 1998;Cross et al, 2010;Gardner et al, 2010;Kilminster and Jolly, 2000;Lindahl and Norberg, 2002;Sloan, 1999;White et al, 1998) and examples included:…”
Section: Task Oriented Contentmentioning
confidence: 99%
“…Other factors relevant to supervision can be described in terms of personal characteristics that build on the relationship and communication between supervisor and students (20). Studies by White et al and Scanlon & Weir (13,21) highlight the fact that nurses found it difficult to make time for supervision and that supervision took time away from the patients. It is worth considering whether the nursing students and their supervisors experienced the same thing, namely that PGS sometimes took time away from other educational activities.…”
Section: Process-oriented Group Supervision Issuesmentioning
confidence: 99%